CHILD CUSTODY RIGHTS IN QUR’AN AND HADITS PERSPECTIVES - Auliya Ghazna Nizami (Jurnal Ilmiah Pesantren, 2017)
Custody of the child (hadhanah) became the dispute between the two parties as a result of a divorce. Child custody dispute cases in Indonesia are handled by the Religious Courts, based on source material and formal laws and regulations. The Qur’an does not mention publicly about hadhanah in a separate verse, verse on breastfeeding (radha’ah) and the obligation of a father to support is the nearest verse regarding child custody. Although the obligation to feed and custody are two different things, both of them become the same this when they come to child benefciaries. Disputes over child custody already happened at shahabah’s era, which is when the parties to the dispute are Umar and his wife, and that mediates is Abu Bakr, who was then serving as the Caliph once qadhi-l- qudhat whose capacity is to mediate a dispute.rights